Pentablock Copolymer from Tetracomponent Monomer Mixture Using a Switchable Dizinc Catalyst - Chen, Thomas T. D; Zhu, Yunqing; Williams, Charlotte K (Macromolecules, 2018)
Well-defined pentablock copolymers are prepared using a single catalyst, in one pot, from four different monomers: anhydride, epoxide, lactone, and CO2. The dizinc catalyst bridges three distinct polymerization cycles and performs a double switch in polymerization mechanism to produce pentablock copolymers. The new materials are hydroxyl-telechelic and are efficiently postfunctionalized to introduce polar and nonpolar side-chains.